Non-invasive ventilation provides adequate gas exchange minimizing pulmonary and extrapulmonary complications - Yu. S. Aleksandrovich; S. B. Dalzhinova; K. V. Pshenisnov; I. V. Aleksandrovich (Вестник анестезиологии и реаниматологии, 2020)
The objective: to evaluate the effectiveness of NIPPV (nasal intermittent positive pressure ventilation) and NHFOV (nasal high-frequency oscillatory ventilation) modes in newborns in the delivery room depending on the gestation period.Subjects and methods. A prospective randomized study included 88 premature newborns with the body mass of 1,405 (1,085–1,760) gr. and gestation period 31 (29–32) weeks. In children of the first group, the NIPPV mode was used, and in the second group – NHFOV. Children of each group were divided into subgroups: subgroup 1 consisted of newborns with a gestation period of 30–32 weeks, subgroup 2 – 26–29 weeks.Results. The need for the traditional ventilator was significantly greater in the group of NIPPV – 15 children, compared to the group of NHFOV – 2 children (p = 0.001). In the same subgroup, statistically significant differences were found in the frequency of bronchopulmonary dysplasia (BPD) and intraventricular hemorrhage (IVH) (p < 0.05). In particular, in the NIPPV group, BPD was registered in 33.3% of cases, while in the NHFOV group – 3.7% (p = 0.001). In children a gestation period of 26–29 weeks, the opposite results were noted. Retinopathy of prematurity was detected in 80% (12) of children on NHFOV and 12.5% (2) who received NIPPV (p = 0,001)). There were also statistically significant differences in the frequency of BPD formation – 9 cases in the first group, 13 cases in the second group (p = 0.04).Conclusion. The use of NIPPV as a starting method of respiratory support is indicated to newborns with the gestation age of 26–29 weeks, and while in newborns with the gestation period of 30–32 weeks, the use of NHFOV is highly effective.